PENGAJARAN AGAMA KATOLIK MENUMBUHKAN KARAKTER KRISTIANI KASIH, RELA BERKORBAN, DAN DAMAI PADA DIRI SISWA - Roymundus Tulus Jatmiko; Ola Rongan Wilhelmus (Bahasa Indonesia, 2024)
Catholic Religious Education in schools is a compulsory subject given by an educator to educate and foster students to develop into individuals with good intellectual and character. One of the goals of Catholic religious education is to foster Christian character in students in addition to developing intellectual abilities. Christian character is a spiritual seed embedded in the self and heart of each individual based on faith in Jesus Christ. Cultivating Christian character through Catholic religious education is an important effort that needs to be done by a Catholic religious teacher as an educator so that students can grow into individuals with Christian character. This study was conducted with the aim of exploring which Christian characters grow as a result of Catholic religious education in schools. This study uses a qualitative research method with a phenomenological approach. The informants in this study were seven Catholic religious teachers who were still actively teaching at high schools in Madiun City. The research data analysis activities included reading all research data, reducing research data, presenting research data, interpreting research data, drawing conclusions on the results of research data analysis, and verifying research data. The contribution to this study is to complete and present the Christian character that grows through Catholic teaching that has not been in previous research. The results of this study indicate that the impact produced in efforts to grow and shape the Christian character of students through Catholic teaching in schools is the development of characters of love, sacrifice, and peace in students.